IMPACT OF BOTANICAL INSECTICIDES DERIVED FROM Pangium edule Reinw AND Annona muricata L. SEED EXTRACTS ON THE “GAY GANTUNG” DIAMONDBACK MOTH, Plutella xylostella L. - Ernest Hanny Sakul (Agrotech Journal, 2017)
Insecticidal properties of fractioned extracts from Pangium edule Reinw seed and Annona muricata seed against Plutella xylostella larvae were investigated in the laboratory. The study was initiated to investigate the possibility of using botanical pesticides to control P.xylostella, a serious cosmopolitan pest of crucifer plants. The study aims to determine the most effective concentration and the most active extract;  to evaluate the different extract concentrations on the treated larvae; and to characterize the phytochemical contents of the most effective extracts fraction. The study was an experiment initiated by test of phytochemical screening test in order to discover the presence of secondary metabolites in the extracts. It was followed by the test of mortality of the diamondback moth larvae. Furthermore, the extracts hexane fraction and etanol fraction, were conducted with completely randomized design; The LC50 values were determined following probit analysis, the data were treated in the software programme IBM Statistic SPSS 20. Results showed that n-hexane fraction is the most effective againts larvae (LC50-48h = 12,71 mg/L) from P.edule seed extract, (LC50-48h = 50,81 mg/L) from A.muricata seed extract. Larva mortality was highest using 1000 ppm n-hexane fraction (96,6%) derived from P.edule seed extract, (93,3%) derived from A.muricata seed extract. The ethanol fraction tested positive for alkaloid, saponins, flavonoids, terpenoids, phenol and tannins. N-hexane fraction of P.edule seed extract, and A.muricata seed extract are an effective botanical insecticides exhibiting larvicidal and antifeedant properties against P.xylostella thus it can be alternative to synthethic insecticides. Results indicate that these botanical insecticides have good possibilities for control of P.xylostella. Further work is necessary to evaluate and characterize the active components of the extract fractions and its efficacy in the fieldInsecticidal properties of fractioned extracts from Pangium edule Reinw seed and Annona muricata seed against Plutella xylostella larvae were investigated in the laboratory. The study was initiated to investigate the possibility of using botanical pesticides to control P.xylostella, a serious cosmopolitan pest of crucifer plants. The study aims to determine the most effective concentration and the most active extract;  to evaluate the different extract concentrations on the treated larvae; and to characterize the phytochemical contents of the most effective extracts fraction. The study was an experiment initiated by test of phytochemical screening test in order to discover the presence of secondary metabolites in the extracts. It was followed by the test of mortality of the diamondback moth larvae. Furthermore, the extracts hexane fraction and etanol fraction, were conducted with completely randomized design; The LC50 values were determined following probit analysis, the data were treated in the software programme IBM Statistic SPSS 20. Results showed that n-hexane fraction is the most effective againts larvae (LC50-48h = 12,71 mg/L) from P.edule seed extract, (LC50-48h = 50,81 mg/L) from A.muricata seed extract. Larva mortality was highest using 1000 ppm n-hexane fraction (96,6%) derived from P.edule seed extract, (93,3%) derived from A.muricata seed extract. The ethanol fraction tested positive for alkaloid, saponins, flavonoids, terpenoids, phenol and tannins. N-hexane fraction of P.edule seed extract, and A.muricata seed extract are an effective botanical insecticides exhibiting larvicidal and antifeedant properties against P.xylostella thus it can be alternative to synthethic insecticides. Results indicate that these botanical insecticides have good possibilities for control of P.xylostella. Further work is necessary to evaluate and characterize the active components of the extract fractions and its efficacy in the field